Metodologi Penelitian Dengan Pendekatan Mixed Methods Di Ilmu Al-Qur’an Dan Tafsir - Haryanto Haryanto (Journal of Innovative and Creativity, 2025)
The mixed methods approach in the study of the Qur'an and Tafsir has become increasingly relevant along with the complexity of the study of sacred texts and the accompanying social realities. The problem that often arises is the limitation of a single approach in explaining the meaning of verses in depth while describing the pattern of understanding of society at large. This paper aims to describe the basic concept, design, and stages of applying mixed methods in the study of Qur'an and Tafsir. The method used is in the form of literature studies with a normative-conceptual approach through the review of books, scientific articles, and relevant methodological documents. The results of the discussion showed that the combination of quantitative and qualitative data was able to produce a more complete understanding, both in terms of the analysis of the Qur'an text and the response and practice of interpretation in the community. This approach allows for systematic data integration, maintaining the validity of findings, and paying attention to scientific ethical aspects. Thus, mixed methods can be an effective methodological framework in developing the study of Qur'an and Tafsir in a more contextual and responsible manner.